Statistical Research of Attracting of Foreign Direct Investment in Ukraine - I. М. Krepchuk (Статистика України, 2015)
The objective of the study is to analyze the peculiar features of foreign direct investment (FDI) in Ukraine, outline the problems related with foreign investing in Ukraine and formulate recommendations on their potential solutions.